INFORMATION TECHNOLOGY GOVERNANCE IN ADVISORY AND ECONOMIC DEVELOPMENT SECTOR USING COBIT 5 FRAMEWORK - Arie Vatresia; Ruvita Faurina; Diky Kurnia Ramadhan (Informatika, Universitas Jenderal Soedirman, 2022)
Bank Indonesia is the central bank of the Republic of Indonesia and an independent state institution, free from interference from the Government or other parties. Bank Indonesia Bengkulu City has a field of Advisory and Economic Development, which uses information technology to handle and assist operational activities. However, there is no clarity regarding the level of the company's ability to manage information technology. This has an impact on the use of IT that is not in line with company goals. Based on these problems, it is necessary to have a capability level in managing information technology using the COBIT framework, to assist companies in utilizing IT to be in line with company goals, through improving quality and value and simplifying the implementation of an organization's process flow from the information technology perspective. So the researchers chose COBIT as the framework that will be used in this research. From the results of the study, it was obtained that the Capability level got a level 4 value for the as is state. Meanwhile, for the condition of Bank Indonesia Bengkulu Province in the Advisory and Economic Development Sector, it expects to reach level 5. Gap analysis is determined by the condition of the current level with the expected level, where the current level is 4 and the expected level is 5 so that the results obtained The analysis gap is 1. This means that Bank Indonesia Bengkulu Province in the Advisory and Economic Development Sector must meet the requirements for process capability indicators at level 5 which have not been met. Such as constantly developing new technologies through innovative ideas based on the company's information technology potential.